Trade in Intermediate Goods and International Specialization - John M. Hartwick (Queen's University, Department of Economics, 1993)
We characterize the multiplicity of patterns of trade in the neo-classical two country, two factor, two final good model extended to incorporate an essential intermediate good. With factor price equalization and no trade in the intermediate good, there are no gains from trade by opening up the world to trade in the intermediate good. However, with factor price equalization and trade in the intermediate good, there can be losses from closing off trade in the intermediate good. Examples are presented. We note that there are definable patterns of specialization for identical countries, given "compulsory" trade in intermediate goods between them. we also examine the cases of three primary factors and two essential intermediate goods.
Keywords: 330